2016
DOI: 10.1080/21580103.2015.1107627
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between above-ground and below-ground biomass of 13-year-oldPinus densifloraS. et Z. planted in a post-fire area in Samcheok

Abstract: View related articles View Crossmark data Citing articles: 4 View citing articles Correlation between above-ground and below-ground biomass of 13-year-old Pinus densiflora S. et Z. planted in a post-fire area in Samcheok

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This species accounts for approximately 23% of South Korean forest cover and 57% of the nation's coniferous forests, and is the most widely established plantation species (Korea Forest Service 2015). Accordingly, improving the health and productivity of Pinus densiflora forests is vital to the current Korean forestry and environmental management (Kim et al 2012;Kim et al 2016a). We specifically hypothesized that strong thinning intensity would have greater effects on microbial biomass and enzyme activity than comparatively light thinning intensity because of differences in soil C and N availability.…”
Section: Introductionmentioning
confidence: 99%
“…This species accounts for approximately 23% of South Korean forest cover and 57% of the nation's coniferous forests, and is the most widely established plantation species (Korea Forest Service 2015). Accordingly, improving the health and productivity of Pinus densiflora forests is vital to the current Korean forestry and environmental management (Kim et al 2012;Kim et al 2016a). We specifically hypothesized that strong thinning intensity would have greater effects on microbial biomass and enzyme activity than comparatively light thinning intensity because of differences in soil C and N availability.…”
Section: Introductionmentioning
confidence: 99%
“…forests. This species accounts for approximately half of the coniferous forest cover in South Korea and is used for various purposes [14,15]. Studying the roles of pine CWD is important, given that forest management activities and outbreak of pine wilt disease in South Korea can generate large volumes of pine CWD [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the higher leaf biomass of Chinese fir found in mixed forests had a greater percentage of deep soil water uptake than in the pure forest. Additionally, some studies indicated that greater light interception by trees with higher leaf biomass allowed them to afford the carbon costs of deeper fine-root growth ( Kim et al, 2016 ; Brum et al, 2018 ). These explained why Chinese fir in mixed forests extracted a higher percentage of deep soil water.…”
Section: Discussionmentioning
confidence: 99%